Ibn Rushd's Epistemology of Ijtihad in the Completion of Fiqh Ikhtilaf (Study of the Book of Bidayah Al-Mujtahid, Chapter of Worship) - Fauzi, Muhammad Rezky; Bakri, Muammar; Shuhufi, Muhammad (Pascasarjana UIN Alauddin Makassar, 2023)
This study analyzes the nature and concept of Ibn Rushd's ijtihad in completing fiqh ikhtilaf among the ulama. He is known for his expertise in philosophy, logic, medical, and the fields of jurisprudence and jurisprudence (Islamic law). It can be proven in his monumental work